2022
DOI: 10.1016/j.ejrad.2021.110107
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of 2-[18F]FDG PET-CT in metastatic melanoma patients receiving immunotherapy

Abstract: The 2-fluorodeoxyglucose positron emission tomography/computed tomography (2-[ 18 F]FDG PET/CT) is used for the evaluation of response to immunotherapy in malignant melanoma. Here, we evaluated the prognostic value of various metabolic parameters in baseline and different time points after therapy. Methods: In this retrospective study, 51 metastatic melanoma patients, who had received immunotherapy, were included. Patients with baseline and two follow-up 2-[ 18 F]FDG PET/CT studies (3 and 6 months after therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…These specific parameters were not commonly reviewed in our patient cohort. Prognostication using 18 F-FDG PET/CT was also reviewed by Schweigoffer-Zwink et al, who demonstrated that metabolic parameters in patients with advanced cutaneous melanoma were predictive for survival in melanoma patients undergoing immunotherapy [23]. This study also found that tumor-to-background values had a stronger predictive value than MTV and TLG.…”
Section: Discussionmentioning
confidence: 70%
“…These specific parameters were not commonly reviewed in our patient cohort. Prognostication using 18 F-FDG PET/CT was also reviewed by Schweigoffer-Zwink et al, who demonstrated that metabolic parameters in patients with advanced cutaneous melanoma were predictive for survival in melanoma patients undergoing immunotherapy [23]. This study also found that tumor-to-background values had a stronger predictive value than MTV and TLG.…”
Section: Discussionmentioning
confidence: 70%
“…However, their clinical utility remains controversial, and to the best of our knowledge, only one study applied the imPERCIST5 criteria to a series of patients treated with ipilimumab, and none in patients on first-line antiPD1 (or anti PD1/anti CTLA4 combination) for advanced/metastatic melanoma [16]. Moreover, FDG PET-derived metabolic volume seems to be a highly promising approach as a prognostic factor on baseline FDG PET, as well as in the follow-up FDG PET examinations [19][20][21][22][23][24]. We investigated whether these two PET/CT criteria (PERCIST5 and imPERCIST5) had prognostic value in patients receiving first-line ICI for advanced or metastatic melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade, molecular imaging techniques such as single photon emission computed tomography (SPECT/CT) and positron emission tomography (PET) have been extensively investigated to provide additional diagnostic information and help identify specific disease mechanisms in tumors, which consolidated their position in the diagnostic strategy of human cutaneous tumors [ 349 ]. The signaling pathways and molecular targets that may be harnessed for molecular imaging in cancer are glucose metabolism [ 255 ], integrin α v β 3 [ 271 ], melanocortin-1 receptor [ 332 ], PD-1/PD-L1 axis [ 272 ], and hence several other biochemical and molecular markers related to immune response and angiogenesis reside in the area of preclinical development [ 360 ]. Although both imaging modalities may be used to assess all skin cancer subtypes, anatomical imaging may be more relevant to NMSC.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its usefulness in CM staging and prognosis, FDG PET has largely been used for evaluating the therapeutic responses in patients receiving systemic therapy, especially ICIs [ 255 , 256 ]. One study conducted by Ito et al reported that whole-body MTV obtained from baseline PET/CT scans might be a valuable prognostic biomarker among other clinical prognostic factors in melanoma patients treated with ipilimumab [ 257 ].…”
Section: Molecular Imaging Techniquesmentioning
confidence: 99%